Supply and Demand for Cereals in Bangladesh: 2010–2030 - Ganesh-Kumar, Anand; Prasad, Sanjay K.; Pullabhotla, Hemant (International Food Policy Research Institute, 2012)
In this study we attempt to provide forecasts of the demand and supply of cereals in Bangladesh for the period 2015–2030, focusing on rice the main staple in Bangladeshi diets and also the most important crop in Bangladesh’s agriculture. A detailed model of the supply of rice in the three main rice growing seasons—aman, aus, and boro—is built up through separate acreage and yield functions, which are estimated with data from the Bangladesh Bureau of Statistics. On the demand side, the projections made here consider both direct demand by households and also indirect demand.